INCREASING TEACHERS' COMPETENCE IN USING LEARNING MEDIA THROUGH ACADEMIC SUPERVISION AT SDN 05 AIR SANTOK - Mis Elis (LPPM Ekasakti University, 2022)
This research is a school action research (PTS) which raises about how teachers can use existing learning media in the learning process in the classroom with the intention of increasing the quality of learning carried out in the classroom and the evaluation is carried out through the supervision of the principal in the classroom when learning. This school action research activity was carried out at SDN 05 Air Santok for 3 months, starting from March to May 2019 by going through cycle stages. The purpose of this school action research (PTS) is to determine the extent to which the supervision carried out by the principal followed by the provision of guidance/treatment to the target teachers can improve the competence of these teachers in applying learning models in the classroom. In this school action research (PTS) it was conducted in 2 cycles, from the results of the actions taken it was proven to be able to increase teacher competence by achieving ideal standards. In the first cycle, the increase in teacher competence after classroom supervision was carried out after coaching on the use of new learning media reached about 33.33% in the second cycle, it could increase to 100%. The average score obtained after class supervision in the first cycle was 63.30 and increased in the second cycle to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in the first cycle reached 33.33% and in the second cycle increased to 100%. The results of this school action research show that the coaching of the principal can improve the competence of teachers in using learning media in the learning process.